SOME GEOMETRIC PROPERTIES OF A NEW DIFFERENCE SEQUENCE SPACE INVOLVING LACUNARY SEQUENCES - Karakas, Murat; Et, Mikail; Karakaya, Vatan (Springer, 2013)
In this paper, we define a new generalized difference sequence space involving lacunary sequence. Then, we examine k-NUC property and property (beta) for this space and also show that it is not rotund where p = (p(r)) is a bounded sequence of positive real numbers with p(r) >= 1 for all r is an element of N.
Keywords: difference sequence space; lacunary sequence; k-NUC property; rotundity; Luxemburg norm